2016
DOI: 10.1007/s40415-016-0309-4
|View full text |Cite
|
Sign up to set email alerts
|

Drought-stress tolerance in three semi-arid species used to recover logged areas

Abstract: We subjected seedlings from three tree species from the semi-arid ''Caatinga'' biome to water deficiency and rehydration. The species were Bauhinia monandra K. and Hymenaea courbaril L., (both Fabaceae), and Tabebuia aurea (Bignoniaceae). Seedlings were kept under water restriction until photosynthesis decreased to values around zero. Plants were rehydrated and photosynthesis measured until its values reached values of well-watered plants. We measured leaf water potential, maximum quantum yield, and chlorophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Similar results were found by Silva-Pinheiro et al (2016) for seedlings of Bauhinia monandra Kurz (Fabaceae) and Tabebuia aurea (Bignoniaceae), both species found in the Caatinga. The authors observed decreases in the leaf area of these species, resulting in a lower biomass accumulation.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were found by Silva-Pinheiro et al (2016) for seedlings of Bauhinia monandra Kurz (Fabaceae) and Tabebuia aurea (Bignoniaceae), both species found in the Caatinga. The authors observed decreases in the leaf area of these species, resulting in a lower biomass accumulation.…”
Section: Discussionsupporting
confidence: 85%
“…In certain plants, water deficit limits cellular expansion and also slows the budding of leaves and branches, thereby reducing the total leaf area, which represents a water-savings for the plant [10,39,42]. Thus, the shedding of leaves also represents a water-savings since the surface area is reduced, besides minimizing the energy expended on maintenance.…”
Section: Discussionmentioning
confidence: 99%